(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Allergic diseases represent a major health problem worldwide. Allergic rhinitis (AR) is the most common disease among both children and adults. According to WHO, “...more than 40% of the population of developed countries have signs of allergic readiness. Currently, the frequency of allergic rhinitis in the general population is 10–20%, and these figures tend to further increase this disease.